Regulation of coral assemblages: Spatial and temporal variation in the abundance of recruits, juveniles, and adults - Radonirina Lebely Botosoamananto; Gildas Todinanahary; Lahitsiresy Max Gasimandova; Mahery Randrianarivo; Lucie Penin; Mehdi Adjeroud (PLoS ONE, 2025)
Understanding the processes that maintain coral assemblages is of crucial importance given increasing rates of coral mortality on reefs globally. Here, we compared relationships among distribution patterns of recruit, juvenile, and adult corals with distinct life history traits to determine the contribution of early life stages to the structure of adult assemblages at Toliara, southwest Madagascar. Results highlighted a marked spatio-temporal variability in the abundance of all life stages within and between major reef habitats. Indications of stock-recruitment relationships (where the adults drive the abundance of early life stages) were found for Acroporidae, whereas Poritidae and its dominant genus Porites were likely regulated by recruitment-limitation mechanisms (where early life stages drive the abundance of adults), with significant correlations between the abundance of juveniles and those of adults of the subsequent years. We found stronger links between all life stages for Pocilloporidae, indicative of both recruitment-limitation and stock-recruitment relationships. In contrast, no significant correlations were recorded for the category of ‘other’ families, which is likely the result of mixing taxa with different life history traits. In fact, positive correlations between juveniles and adults were found for Galaxea, Cycloseris, and Pavona genera, which made up the ‘other’ category. The discrepancies of regulation processes among coral taxa highlighted here suggest implementing conservation actions that benefit all life stages. Maintaining the biomass of herbivorous fishes and invertebrates to control algal biomass can benefit coral recruitment and decrease mortality of early life stages and adult colonies. Our results also suggest that sites on the outer slope and on patch reefs, which show higher recruitment rates and abundance of adult colonies, could be considered as recruitment hotspots.